2022
DOI: 10.1515/crpm-2021-0079
|View full text |Cite
|
Sign up to set email alerts
|

Massive fetomaternal hemorrhage: a case series and review of literature

Abstract: Objectives Massive fetomaternal hemorrhage (FMH) is a rare and difficult to diagnose event that can have catastrophic outcomes. Although many etiologies have been associated with FMH, the majority of cases are idiopathic and affect uncomplicated pregnancies. The prevailing symptom is decreased fetal movements but some cases are asymptomatic. Changes in the fetal Doppler ultrasound, a sinusoidal cardiotocographic pattern, neonatal anemia, unexplained hydrops or stillbirth can raise suspicion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The authors found a similar incidence of large FMH in singleton and multiple pregnancies [ 25 ]. Moreover, several case reports presented different outcomes [ 2 , 3 , 12 , 26 , 27 , 28 ]. In all the abovementioned published studies, the incidence of a significant FMH was analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found a similar incidence of large FMH in singleton and multiple pregnancies [ 25 ]. Moreover, several case reports presented different outcomes [ 2 , 3 , 12 , 26 , 27 , 28 ]. In all the abovementioned published studies, the incidence of a significant FMH was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of placental barrier interruption, the fetal red blood cells can cross into the maternal circulation [ 2 , 3 , 4 ]. If the mother’s immune system is stimulated by fetal red blood cell antigens, antibodies are produced, which may lead to the development of hemolytic disease of the fetus (HDF).…”
Section: Introductionmentioning
confidence: 99%
“…A common complication of RBC alloimmunization in pregnant women is FMH, which may have devastating consequences to the fetus such as fetal demise, neurologic injury, hydrops, delivery of a severely anaemic infant and stillbirth [41][42][43]. There are more than 60 different RBC antigens, which are commonly referred to as alloimmunization, especially the Rhesus, Kell, Duffy, Kidd, and MNS blood group systems [38].…”
Section: Table 2: Prevalence Of Rbc Alloimmunization In Pregnant Wome...mentioning
confidence: 99%